Prevalence and transmission of leptospiral infection in rats in Malaysia - Mohamed Hassan, Siti Nabila (2012)
Rats are considered as one of the most important sources of leptospirosis as they are present in abundance in many environments. They caused significant economic losses and served as reservoirs for many zoonotic diseases. One of the diseases is leptospirosis which is considered a re-emerging disease in Malaysia. However, knowledge of the epizootic of leptospirosis and leptospiral serovars associated with rats is lacking. The objectives of the study therefore, were to determine the distribution of rats species and their carrier status. In addition to the determination of the seroprevalence of leptospiral infection in rats, the transmission of leptospiral infection from leptospires-contaminated water to rats was also determined. In Malaysia, Rattus tiomanicus was found to be the dominant species found in Malaysian environments and it constitutes 86.0% (420 out of 488 rats) of the rats caught in different types of localities; National Service Training Camps (Kelantan, Terengganu, Malacca and Selangor), oil palm estates (Terengganu and Malacca), Royal Belum rainforest (Perak), suburban areas (Kelantan and Perak) and PULAPOL (Negeri Sembilan). Sixty leptospiral isolates (12.3%) were successfully cultured from the kidneys of the rats caught. Polymerase chain reaction (PCR) assay revealed forty-two (8.6%) of the isolates were pathogenic as disclosed by the 16S primers. Majority of the pathogenic leptospires were isolated from rats caught in the National Service Training Camps (NSTC). The high rate in NSTC posed a major threat to the trainees as they were frequently involved in outdoor activities and exposed to infected environment. Microscopic agglutination test (MAT) and enzyme-linked immunosorbent assay (ELISA) were applied in the detection of leptospiral antibodies in the rat sera. Screening of the rat sera by ELISA disclosed a high seroprevalence (78.1%) of leptospiral infection among the captured rats. Higher prevalence of leptospiral IgG antibodies were observed in the NSTC than other selected places. In Malaysia, little information is available regarding the prevalence of leptospiral serovars in the rat population. Results from the MAT showed leptospiral infection due to eight serovars; icterohaemorrhagiae, canicola, djasiman, bataviae, ballum, australis, pyrogenes and hebdomadis. Icterohaemorrhagiae was seen as the dominant serovar detected in the rat sera. The titers ranged from 1:40 to 1:2560. However, the titers were frequently recorded between 1:40 to 1:80. The highest titer (1:2560) observed belonged to serovar australis. Water contaminated with leptospires was an important source for leptospiral infection in rats. Rats that have been exposed for 10 days with leptospire-contaminated water, appeared healthy and having no symptoms related to leptospiral infection. However, antibody to serovar icterohaemorrhagiae was detected with titer ranged from 1:80 to 1:320. As demonstrated by silver staining method, leptospires were observed from Day 10 to Day 28 in the liver, spleen and kidneys. Inflammation of the hepatocytes and spleen cells were marked by the presence of neutrophils, macrophages and lymphocytes as shown by Hematoxylin and Eosin staining. Interstitial nephritis was observed in the infected kidneys throughout the experiment. Inflammation of the tubules and glomeruli in the kidneys indicated chronic infection of leptospirosis in the infected rats. The findings of the present study provided information about the seroprevalence and carrier status of rats for pathogenic leptospires in Penisular Malaysia and their roles as reservoirs for the organisms. Leptospiral transmission within rat population occurs mainly through contact with leptospires-contaminated environments. Infected rats may become carriers and maintained infection for a long period, thus ensure the continuous circulation of leptospires in nature. Therefore, control of rat population is crucial in minimizing the risk of transmitting leptospirosis to human.